Personality disorders in personological perspective - Gasiul, Henryk (Studia Psychologica: Theoria et praxis, 2004)
The author considers possibility of interpretation personality disorders in the light of personological approach. The interaction paradigm of personality becomes a basis for further conceptual resolutions. This paradigm presupposes that in creation of personality motivational and cognitive processes play the main role. Nevertheless, the fundamental question is to determine what kind of motives are essential as sources of anticipated disorders. The way these motives are realized in interaction with other persons would shape an opportunity to create a form of diathesis which in a situation of stress experiencing could lead to some form of personality disorder. The way of realization of these motives is also the cause of creation of personal consciousness and meanings. Referring to his earlier considerations the author assumes that the essential are the motives connected to “me”, like for example striving for dignity, for identity. It is supposed that personality disorders would be the outcome of frustration of these motives. The frustrated “me” motives provoke to concentrate on these kinds of objects which recover the possibility of their realization. In consequence, a personality disorder would be a form of preference of behaviors which allow to fulfill essential personal motives.